The Evaluation of the European Union's Middle East Policy - Ultan, Mehlika Özlem (Journal of Applied And Theoretical Social Sciences, 2022)
The efforts of the European Union to develop a common foreign policy did not result successfully in the Middle East region. However, the EU acts within the framework of the ‘European Neighborhood Policy’ and the ‘Union for the Mediterranean’ policies in order to ensure peace, security and stability in this neighboring region. Therefore, it can be stated that the EU's Middle East policy is shaped by the European Neighborhood Policy. In this context, the study aims to show that the Union has not put forward a common foreign policy towards the Middle East and to evaluate whether the Union is effective in the region through different policies. Within the scope of the study, the policies implemented by the Union in the Middle East region before and after the Arab Spring will be examined. Thus, it will be revealed that the EU's Middle East policy, which was initially developed to ensure peace in the Middle East, has given more importance to energy, migration and security issues in recent years.